Comprehensive assessment of meta-analysis and contingent valuation technique for sustainable management of wetland of Middle Ganga Plain - Roy, Malabika Biswas; Kumar, Abhishek; Chatterjee, Debanjana; Halder, Sudipa (Quaestiones Geographicae, 2022)
In this study, the functions and threats of Suraha Tal Wetland are identified by the stated preference method and weightage is given according to their rank. The objective of the study is to determine the total economic value of Suraha Tal Wetland. The direct value can be drawn from the market price and from a survey of the stakeholders. Suraha Tal Wetland is also famous for the presence of the Jai Prakash Narayan Birds Sanctuary, which makes it a biodiversity-enriched area. The indirect value has been drawn from a review of the literature on Suraha Tal Wetland and the relevance of this literature is justified through the comprehensive meta-analysis (CMA) software. The total valuation of the wetland has been calculated. The paper concludes with suggestions for a few management strategies for better wetland management.